Excellence and equity in high-performing education systems: policy lessons from Singapore and Hong Kong / Excelencia y equidad en sistemas educativos de alto rendimiento: lecciones de las políticas educativas en Singapur y Hong Kong. Issue 2 (3rd April 2018) - Gopinathan, Saravanan; Lee, Michael H.
Abstract: In recent years, both Singapore and Hong Kong have been ranked top in international education rankings. They are widely admired as high-performing education systems (HPES) and, not surprisingly, among the best education systems in the world. The success stories of Singapore and Hong Kong education have aroused widespread attention internationally among different stakeholders, such as policymakers, researchers and practitioners, to investigate if it is possible for their policies and practices to be learned and borrowed by other countries. In this article, we stress the importance of context in understanding policy phenomena and possibilities for policy transfer. The Singapore and Hong Kong education systems are facing critical issues such as the economization of education, educational disparities and the paradigm shift from meritocracy to parentocracy. How well they deal with these policy issues will determine if their present international standing continues into the future. This article provides a critical review of their education policies to explore how these policies can be refined and adjusted in order to cope with the challenges facing both education systems.